Molecular mechanisms of repulsive guidance molecule signalling - Healey, E (2015)
Repulsive Guidance Molecules (RGMs) control fundamental and diverse cellular processes including axon guidance, immune cell regulation and systemic iron metabolism. RGM dysfunction has been linked to diseases such as multiple sclerosis, cancer and the iron overload disorder juvenile hemochromatosis (JHH). RGMs signal by binding directly to the transmembrane receptor Neogenin (NEO1) to trigger cytoskeleton rearrangements and subsequent axon repulsion. Additionally, RGMs are important activators of the essential developmental Bone Morphogenetic Protein (BMP) signalling pathway. RGM-activated BMP signalling is crucial for the regulation of iron metabolism and mutations in RGMC cause JHH. This thesis outlines structural and functional studies of the molecular mechanisms of RGM signalling. In Chapter 3, an analysis of an RGMB-NEO1 crystal structure is presented. Combined with mutagenesis studies, analytical ultracentrifugation experiments and neurite outgrowth assays, this allowed a mechanism for RGM signalling through NEO1 to be proposed. RGM acts as a molecular staple, bringing together the juxtamembrane regions of two NEO1 receptors to activate downstream signalling. In Chapter 4, crystal structures of the N-terminal domains of all RGM family members in complex with the BMP2 ligand are presented. Together with biophysical and cellular assays these structures allowed an endocytosis-linked mechanism for RGM-activated BMP signalling to be proposed, which is dependent on the subcellular localisation of the BMP-receptors. The work outlined in both of these chapters also revealed a molecular rationale for the disease-causing mechanism of RGMC JHH-linked mutations. In Chapter 5, the crystal structure of the ternary BMP2-RGMBNEO1 complex is described along with super-resolution uorescence microscopy data demonstrating BMP-induced clustering of RGM-NEO1 complexes in the membrane. In summary, this work sheds light on the molecular mechanisms of RGM signalling through NEO1 and BMPs, and demonstrates for the first time that RGM forms a structural bridge between these two fundamental signalling pathways.